Pengaruh Profesional Guru Dalam Penggunaan Media Video Interaktif Terhadap Motivasi Belajar Dan Aktivitas Belajar di SMP - Arestalia, Nike Pebri; Sumiharsono, Rudy; Triwahyuni , Eges (LP. Ma'arif Janggan Magetan, 2023)
The problem in this research is whether there is an influence of training methods and the use of video media together on the reaction speed of teenage volleyball athletes in Class 1) bottom serve, 2) bottom pass, 3) top pass. Variable stalk muscle. Causal quantitative research design. The method for determining the area is purposive sampling area. Population research techniques population research. Data collection techniques: 1) Observation, 2) Interview, 3) Documentary, 4) Questionnaire, 5) Test. Data analysis 1) Instrument test, 2) Classic assumption test, 3) hypothesis test. The results of the t test on reaction speed (0.737>0.682), the t test of the use of video media on reaction speed (0.855>0.682), the results of the F test of t test of training methods and the use of video media on reaction speed (11.384>2.87). So it can be concluded that the training method and video media influence reaction speed so that H0 is rejected.